If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -6(-5x + 6) = 94 Reorder the terms: -4x + -6(6 + -5x) = 94 -4x + (6 * -6 + -5x * -6) = 94 -4x + (-36 + 30x) = 94 Reorder the terms: -36 + -4x + 30x = 94 Combine like terms: -4x + 30x = 26x -36 + 26x = 94 Solving -36 + 26x = 94 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 26x = 94 + 36 Combine like terms: -36 + 36 = 0 0 + 26x = 94 + 36 26x = 94 + 36 Combine like terms: 94 + 36 = 130 26x = 130 Divide each side by '26'. x = 5 Simplifying x = 5
| 5x^2+21x=-18 | | 6x(6x)+1=1 | | 7x-3(3x+7)=-9 | | 0(0)-4=4 | | -4+4(-4x+9)=-64 | | 5x^2-8x=6 | | 3x+2(x-5)=4 | | -4+4(-4x+9)=-74 | | 2y+2x=2 | | 5x^2+5=-13x | | 9x^3-3x^2-2x=0 | | -4x-4(-4x+9)=-64 | | 9x^2+16=-25 | | 4(3w-2)=52 | | 2ln(x)-ln(x+2)=0 | | 3y+5.2=2-5 | | 6x+30-5x=25 | | 3(3x-2)=25.3 | | 12xy-xy-y^2= | | x-0.20x=25 | | 3c^2-5c-12=0 | | -2x+3(2x+7)=-23 | | -x+3y=-12 | | y^2-28=3y | | -9+4x=2x+9 | | 6w^2+5wp-21p^2= | | x-67=-6x+17 | | 5a=7-b | | -31+6x=-3x+32 | | 10=2m-4m | | b^2-23b+60=0 | | 16+8p=24.00 |